Adaptation of the Beliefs about Well-Being Scale to the Spanish population. - San-Martín-García, Jesús Emilio; Perles-Novas, Fabiola; García-Martín, Miguel Ángel; Canto-Ortiz, Jesús María (Universidad de Murcia, 2021)
The study of happiness and well-being is receiving increased at tention in different fields. Recent research into well-being has focused on delving deeper into the individual’s conception about the experience of well-being. McMahan and Estes (2011a) created a scale that assesses lay conceptions of well-being based on four dimensions: the experience of pleasure, avoidance of negative experience, self-development and contribu tion to others. The goal of this study was to adapt this scale, the Beliefs about Well-Being Scale (BWBS), to the Spanish population. The sample consisted of 1,024 participants from the general population ranging in age interval from 17 to 87 years old. The confirmatory factorial analysis results in a structure of four dimensions, similar to the original scale, although in the adaptation of the scale the items decrease from 16 to 12. The results of the reliability analysis reveal indexes similar to those of the original scale. These results confirm the validity of Beliefs about Well-Being Scale with general population in a cultural context different from the original study. This will allow cross-cultural studies to analyze the influence of culture in the perception of well-being.
Keywords: Felicidad; Hedonismo; Calidad de vida; Well-being; Happiness; Eudaimonia; Hedonism